Broadband blue light for Optical Coherence Microscopy - Maliszewska, Sylwia; Wojtkowski, Maciej (Photonics Letters of Poland, 2011)
Optical coherence microscopy (OCM) is relatively new, noninvasive method of biomedical imaging. It uses Michelson interferometer to locate successive layers in tissue and enables reconstructing cross-sectional images that can be useful for medical diagnosis. In this work, we propose to develop new light sources for OCM to increase the resolution of images by introducing blue light. To achieve this goal, we decided to test a method known as achromatic second harmonic generation in our own, new configuration. Full Text: PDF References: A.M. Zysk et al., "Optical coherence tomography: a review of clinical development from bench to bedside", J Biomed Opt 12, 051403 (2007). [CrossRef] M. Wojtkowski, "High-speed optical coherence tomography: basics and applications", Appl Opt 49, D30 (2010). [CrossRef] D. Huang et al., "Optical coherence tomography", Science 254, 1178 (1991). [CrossRef] A.F. Fercher et al., "Optical coherence tomography - principles and applications", Reports on Progress in Physics 66, 239 (2003). [CrossRef] A.D. Aguirre et al., "High-resolution optical coherence microscopy for high-speed, in vivo cellular imaging", Opt. Lett. 28, 2064 (2003). [CrossRef] M.V. Sarunic, S. Weinberg, J.A. Izatt, "Full-field swept-source phase microscopy", Opt. Lett. 31, 1462 (2006). [CrossRef] S.J. Kirkpatrick, R.K. Wang, D.D. Duncan, "OCT-based elastography for large and small deformations", Opt. Exp. 14, 11585 (2006). [CrossRef] J.M. Schmitt, "OCT elastography: imaging microscopic deformation and strain of tissue", Opt. Exp. 3, 199 (1998). [CrossRef] B.F. Kennedy et al., "In vivo three-dimensional optical coherence elastography", Opt Exp. 19, 6623 (2011). [CrossRef] D.C. Adler et al., "Photothermal detection of gold nanoparticles using phase-sensitive optical coherence tomography", Optics Exp. 16, 4376 (2008). [CrossRef] A.L. Oldenburg et al., "Phase-resolved magnetomotive OCT for imaging nanomolar concentrations of magnetic nanoparticles in tissues", Optics Exp. 16, 11525 (2008). [CrossRef] M. Wojtkowski, Obrazowanie za pomocą tomografii optycznej OCT z detekcjąfourierowską(Wydawnictwo Naukowe UMK, Toruń 2009). P. Wnuk, Y. Stepanenko, and C. Radzewicz, "High gain broadband amplification of ultraviolet pulses in optical parametric chirped pulse amplifier", Opt Exp. 18, 7911 (2010). [CrossRef]